A high cell density perfusion process for Modified Vaccinia virus Ankara production: Process integration with inline DNA digestion and cost analysis. Issue 12 (23rd September 2021) - Gränicher, Gwendal; Babakhani, Masoud; Göbel, Sven; Jordan, Ingo; Marichal‐Gallardo, Pavel; Genzel, Yvonne; Reichl, Udo
Abstract: By integrating continuous cell cultures with continuous purification methods, process yields and product quality attributes have been improved over the last 10 years for recombinant protein production. However, for the production of viral vectors such as Modified Vaccinia virus Ankara (MVA), no such studies have been reported although there is an increasing need to meet the requirements for a rising number of clinical trials against infectious or neoplastic diseases. Here, we present for the first time a scalable suspension cell (AGE1.CR.pIX cells) culture‐based perfusion process in bioreactors integrating continuous virus harvesting through an acoustic settler with semi‐continuous chromatographic purification. This allowed obtaining purified MVA particles with a space‐time yield more than 600% higher for the integrated perfusion process (1.05 × 10 11 TCID50 /Lbioreactor /day) compared to the integrated batch process. Without further optimization, purification by membrane‐based steric exclusion chromatography resulted in an overall product recovery of 50.5%. To decrease the level of host cell DNA before chromatography, a novel inline continuous DNA digestion step was integrated into the process train. A detailed cost analysis comparing integrated production in batch versus production in perfusion mode showed that the cost per dose for MVA was reduced by nearly one‐third using this intensified small‐scale process. Abstract : In this work, we present a scalable suspension cell culture‐based perfusion process in bioreactors integrating continuous viral vector harvesting through an acoustic settler with semi‐continuous chromatographic purification achieving an overall product recovery of 50.5% without further optimization. Subsequent cost analysis comparing integrated production in batch versus production in perfusion mode showed that the cost per dose for Modified Vaccinia virus Ankara was reduced by nearly one third using this intensified small‐scale process.